2002
DOI: 10.5713/ajas.2002.963
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production, Blood Metabolites and Circulatory Levels of Hormones in Crossbred Goats

Abstract: Collection and analysis of milk and blood samplesAt fortnightly intervals (periods), milk samples were collected from individual goat throughout the experimental period of 150 days duration. Aliquots of milk in proportion to yield from each milking of individual goat were composited for analysis of milk constituents. In milk samples, fat was determined volumetrically by Gerber's method (I.S.I. 1958), protein by the method of Singhal and Des Raj (1989) and lactose by picric acid method (Perry and Doon, 1950). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
4
1
0
Order By: Relevance
“…The blood glucose concentrations were consistent with feed intake for all treatments. These levels are consistent with Singh & Ludri (2002) reporting the blood glucose level in 30, 60 and 90 lactation periods between 49-57 mg/dl. Range of glucose levels of 60 to 71 mg/dl in several breeds of the goat during lacatatin maintained under intensive production system was reported by Mohammed et al (2016).…”
Section: Resultssupporting
confidence: 92%
“…The blood glucose concentrations were consistent with feed intake for all treatments. These levels are consistent with Singh & Ludri (2002) reporting the blood glucose level in 30, 60 and 90 lactation periods between 49-57 mg/dl. Range of glucose levels of 60 to 71 mg/dl in several breeds of the goat during lacatatin maintained under intensive production system was reported by Mohammed et al (2016).…”
Section: Resultssupporting
confidence: 92%
“…From day 77 onwards the values continuously increased up to day 203 and thereafter day 217 from fluctuation was noticed up to end of lactation. Similar findings were observed by Singh and Ludri (2002) and ) who noted that higher value during early stage of lactation. However, contrary finding were recorded by Dalvi et al, (1995) who reported low T 3 concentration before parturition and followed by subsequent increase on day of parturition and declined after calving.…”
Section: Mean ± S E Values Of Hormonal Parameters During Complete Lactation In Hf Crossbred Cows (Table 2)supporting
confidence: 89%
“…The levels of GH was initially high and then declined up to day 63 and then slightly increases up to day 133 and again slight declined up to day 203 and then increase day 217 and thereafter pattern was declined up to the end of lactation. Similar finding of higher value during early stage of lactation were observed by Jindal and Ludri (1990 a ), Singh and Ludri (2002) and ).…”
Section: Mean ± S E Values Of Hormonal Parameters During Complete Lactation In Hf Crossbred Cows (Table 2)supporting
confidence: 88%
See 2 more Smart Citations